Early Detection of Corrosion-Induced Concrete Micro-cracking by Using Nonlinear Ultrasonic Techniques: Possible Influence of Mass Transport Processes - Miguel-Ángel Climent; Marina Miró; Jesús-Nuño Eiras; Pedro Poveda; Guillem de Vera; Enrique-Gonzalo Segovia; Jaime Ramis (Corrosion and Materials Degradation, 2022)
This work presents results allowing an unequivocal correlation of the observations of strong nonlinear elastic features of ultrasonic waves (values of the nonlinearity parameters exceeding the thresholds corresponding to undamaged states), with the critical events of the corrosion-induced surface cracking of reinforced cement-mortar specimens. These observations point to the possibility of the early detection of cracking using nonlinear ultrasonic (NLU) techniques. Experimental evidence is presented on the existence of active net mass transport processes, due to wick action, in the course of the corrosion tests, in the experimental conditions of this work. These phenomena might explain the observed abrupt shifting of the nonlinear parameter values (typically increasing and then decreasing post-peak, even reaching values typical of the undamaged state), and, partially, the high variability obtained for the values of the nonlinear parameters in damaged (cracked) states. Finally, some consequences are derived from the point of view of use of the NLU techniques in engineering practice, i.e., in surveys aimed at evaluating reinforced concrete structures affected by corrosion.